Quality Social Connection as an Active Ingredient in Digital Interventions for Young People With Depression and Anxiety: Systematic Scoping Review and Meta-analysis - Lindsay H Dewa; Emma Lawrance; Lily Roberts; Ellie Brooks-Hall; Hutan Ashrafian; Gianluca Fontana; Paul Aylin (JMIR Publications, 2021)
BackgroundDisrupted social connections may negatively affect youth mental health. In contrast, sustained quality social connections (QSCs) can improve mental health outcomes. However, few studies have examined how these quality connections affect depression and anxiety outcomes within digital interventions, and conceptualization is limited. ObjectiveThe aim of this study is to conceptualize, appraise, and synthesize evidence on QSC within digital interventions (D-QSC) and the impact on depression and anxiety outcomes for young people aged 14-24 years. MethodsA systematic scoping review and meta-analysis was conducted using the Joanna Briggs Institute methodological frameworks and guided by experts with lived experience. Reporting was guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The MEDLINE, Embase, PsycINFO, and CINAHL databases were searched against a comprehensive combination of key concepts on June 24, 2020. The search concepts included young people, digital intervention, depression, anxiety, and social connection. Google was also searched. A reviewer independently screened abstracts and titles and full text, and 9.99% (388/3882) of these were screened by a second reviewer. A narrative synthesis was used to structure the findings on indicators of D-QSC and mechanisms that facilitate the connection. Indicators of D-QSC from the included studies were synthesized to produce a conceptual framework. ResultsOf the 5715 publications identified, 42 (0.73%) were included. Among the included studies, there were 23,319 participants. Indicators that D-QSC was present varied and included relatedness, having a sense of belonging, and connecting to similar people. However, despite the variation, most of the indicators were associated with improved outcomes for depression and anxiety. Negative interactions, loneliness, and feeling ignored indicated that D-QSC was not present. In 24% (10/42) of the applicable studies, a meta-analysis showed a significant decrease in depression (-25.6%, 95% CI -0.352 to -0.160; P<.001) and anxiety (-15.1%, 95% CI -0.251 to -0.051; P=.003) after a D-QSC. Digital mechanisms that helped create a quality connection included anonymity, confidentiality, and peer support. In contrast, mechanisms that hindered the connection included disconnection from the real world and inability to see body language. Data synthesis also identified a 5-component conceptual framework of D-QSC that included rapport, identity and commonality, valued interpersonal dynamic, engagement, and responded to and accepted. ConclusionsD-QSC is an important and underconsidered component for youth depression and anxiety outcomes. Researchers and developers should consider targeting improved QSC between clinicians and young people within digital interventions for depression. Future research should build on our framework to further examine relationships among individual attributes of QSC, various digital interventions, and different populations.